Analisa Strategi Co-Branding Smitten By Pattern Pada Sebelum dan Selama Pandemi COVID-19 - Tyana Anggraeni; Sarah Shafitri (Universitas Bina Sarana Informatika, 2020)
Co-branding is one of strategies used by a brand to increase the brand awareness and brand equity. This strategy is used by Smitten By Pattern, an apparel brand that often collaborates with another local brand such as Woodka and Living Loving in doing the co-branding that leads to sales. This study aims to analyze the co-branding process before and during the pandemic caused by COVID-19 using marketing plan theory. Starts from investigating current target audience identity, situation, and behaviour, examining the marketing strategy and marketing mix, the co-branding process, implementation, also the monitoring and evaluation process to find out the advantages and disadvantages of co-branding. The methodology of this research will be using a qualitative method with a descriptive approach. This study found that there are significant differences between co-branding before and during pandemic caused by COVID-19; Smitten By Pattern have to increase their social media presence because of high number of online audience during pandemic, always providing a storytelling and relatable content for the audience, also getting unpredictably high online sales during pandemic. However, even though online sales in the last few months during pandemic are relatively high, that does not mean it can be compared with additional income by offline activities at the same time in the last year.